COMPARISON OF OUTCOME OF ZYGOMATIC BONE FRACTURE MANAGED BY TWO DIFFERENT TREATMENT PROTOCOLS KEEN’S APPROACH AND PERCUTANEOUS HOOK METHOD. : J Peop Univ Med Health Sci. 2025:15(2), 149-157. http://doi.org/10.46536/jpumhs/2025/15.02.635 - Farzana Lakho1, Muhammad Shahzad2, Tarique Hussain Shaikh3, Aftab Ahmed Kumbhar4 Hafsa Maqbool5, Sadia Abbasi6 , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
OBJECTIVE: The objective of this study was to compare the outcome of zygomatic bone fracture managed by Keens/Buccal sulcus approach and Percutaneous hook method with respect to facial aesthetic and functional occlusal stability. MATERIALS AND METHODS: This randomized control trial was conducted at Department of Oral and Maxillofacial Surgery, Liaquat University of Medical and Health Sciences, Hyderabad/ Jamshoro, Sindh, Pakistan from 5th November 2020 to 13th September 2021. Total 60 patients were included. Postoperative x-rays PNS view or CT scan showed exact approximation of fractured segments. Patients were recalled after 1st, 2nd and on 3rd week for assessment of functional outcome. Mouth opening was measured by metallic ruler. Cheek flattening and facial asymmetry were clinically assessed by Holmes and Mathew’s classification system respectively. Stratification was done using Chi square test considering p-value ≤ 0.05 as significant. RESULTS: Seventy per cent patients had grade-III in Group-A, while 66.7% patients had grade-III in Group-B. 60% patients had class-II in Group-A and 63.3% patients had class-II in Group-B. The cheek flattening grade was insignificantly associated with the study group. The mouth opening class after 1st week was significantly associated with the study group while no significant association was found after 2nd and 3rd week. CONCLUSION: The Keen intraoral approach offers had good functional outcome with the advantage of avoiding skin incisions.